Unlocking creativity : teaching across the curriculum - Fisher, Robert, 1943-; Williams, Mary, 1948- (David Fulton, 2004)
Showing how creativity can be developed across the curriculum, this book offers advice on how to develop children's capacity for creative thinking and achievement and use creativity to increase levels of motivation and self-esteem. Combining the latest research with practical ideas and tasks, this multidimensional book is a must for teachers, students, and educators who wish to know more about creativity in teaching and learning.